2021
DOI: 10.1002/art.41616
|View full text |Cite
|
Sign up to set email alerts
|

American College of Rheumatology Clinical Guidance for Multisystem Inflammatory Syndrome in Children Associated With SARS–CoV‐2 and Hyperinflammation in Pediatric COVID‐19: Version 2

Abstract: Objective. To provide guidance on the management of Multisystem Inflammatory Syndrome in Children (MIS-C), a condition characterized by fever, inflammation, and multiorgan dysfunction that manifests late in the course of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. Recommendations are also provided for children with hyperinflammation during coronavirus disease 2019 (COVID-19), the acute, infectious phase of SARS-CoV-2 infection. Methods. The Task Force was composed of 9 pediatric rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
549
3
83

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 365 publications
(646 citation statements)
references
References 122 publications
(324 reference statements)
11
549
3
83
Order By: Relevance
“…(2) Hypercoagulability: the construction of thrombus can be aided by the inflammation. Severe COVID-19 leads to a cytokine storm as an expression of hyperactive host immune system response to the virus and the inflammation can cause coagulopathy as a consequence of sepsis (Henderson et al 2020;Mangalmurti and Hunter 2020). This event has been termed sepsis-induced coagulopathy (SIC) and is comorbid with high D-dimer levels and elevated fibrinogen (Iba et al 2019;Tang et al 2020).…”
Section: Stroke and Covid-19mentioning
confidence: 99%
“…(2) Hypercoagulability: the construction of thrombus can be aided by the inflammation. Severe COVID-19 leads to a cytokine storm as an expression of hyperactive host immune system response to the virus and the inflammation can cause coagulopathy as a consequence of sepsis (Henderson et al 2020;Mangalmurti and Hunter 2020). This event has been termed sepsis-induced coagulopathy (SIC) and is comorbid with high D-dimer levels and elevated fibrinogen (Iba et al 2019;Tang et al 2020).…”
Section: Stroke and Covid-19mentioning
confidence: 99%
“…10 The trigger for initiating a dysregulated immune response to COVID-19 infection manifesting as MIS-C remains unknown. [1][2][3]8,9 Rostad et al have reported that patients with MIS-C had high titers of SARS-COV-2 receptor binding domain IgG antibodies compared with other hospitalized patients with and without COVID-19 infection, these titers correlated with markers of inflammation and length of stay. 11 In our patient, IgM antibodies were negative suggesting passive transfer of maternal IgG.…”
Section: Discussionmentioning
confidence: 99%
“…When compared with Kawasaki disease (KD), a similar but distinct entity, the patients tend to be older-of Hispanic or African decenthave prominent gastrointestinal and cardiovascular involvement with thrombocytopenia and lymphopenia. 2 In this report, we describe a case of presumptive neonatal MIS-C like disease with the intent of increasing awareness of this possibility in critically ill neonates born to mothers infected with SARS-CoV-2 infection even when the clinical features are atypical.…”
mentioning
confidence: 99%
“…Cron outlined treatment options, which included immunomodulatory agents such as intravenous immunoglobulin infusions, as used for KD, glucocorticoids, anakinra (IL-1 receptor antagonist) and infliximab (a monoclonal antibody to TNF); antimicrobials, including remdesivir and broad-spectrum antibiotics (as some patients' clinical pictures resemble bacterially induced toxic shock syndrome); and, in severe cases, mechanical ventilation, pressor support and anticoagulants 8,9,14,15 . Updated treatment guidelines were published recently by the American College of Rheumatology 16 .…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%
“…To investigate MIS-C from a systems biology perspective, similar to studying COVID-19 in adults, Dusan Bogunovic (Icahn School of Medicine at Mount Sinai) described analyses of about 40 patients treated at Mount Sinai in New York who presented with the symptoms of MIS-C and who met diagnostic criteria 16 . Treatment with an IL-6R blocker and intravenous immunoglobulin led to discharge, usually within 5 days, with universally favorable outcomes.…”
Section: Multisystem Inflammatory Syndrome In Childrenmentioning
confidence: 99%